Moderating role of age in the relationship between ingroup range and intention to help during the COVID-19 pandemic - Inyeong Lee; Hyekyung Park (PLoS ONE, 2025)
This study explored the relationship between the ingroup range of individuals and their willingness to assist various social groups during the COVID-19 pandemic and whether or not age moderates this relationship. A total of 291 South Koreans (Mage = 31.91 years, SD = 11.99) participated in an online survey and provided data on ingroup range, intention to provide help, and age. The results demonstrated that individuals with a broader ingroup range displayed a stronger willingness to distribute quarantine supplies for COVID-19 across diverse social groups (β = .12, p < .05). This finding aligned with the ingroup bias phenomenon, in which individuals tend to favor one’s group. Importantly, age moderated the association between ingroup range and willingness to help (B = −.19, p < .05). Specifically, the intention of younger individuals (θX → Y|(M = −11.985) = 4.40, CI = 1.79–7.01) and middle-aged individuals (θX → Y|(M = .000) = 2.14, CI = .31–3.98) to assist diverse social groups significantly varied according to their ingroup range, whereas no such relationship existed among older individuals (θX → Y|(M = 11.985) = −.11, CI = −2.64–2.42). We provided an in-depth discussion into the potential reasons that underlie the stronger willingness of older individuals to extend aid beyond their ingroup range during the pandemic compared with those of younger individuals. We then suggested strategies for encouraging acts of prosociality during crises, such as the COVID-19 pandemic, which particularly emphasize the pattern observed in younger participants with a narrow ingroup range.